Medical 3D Printing Using Material Jetting: Technology Overview, Medical Applications, and Challenges - Shivum Chokshi; Raghav Gangatirkar; Anish Kandi; Maria DeLeonibus; Mohamed Kamel; Seetharam Chadalavada; Rajul Gupta; Harshitha Munigala; Karthik Tappa; Shayne Kondor; Michael B. Burch; Prashanth Ravi (Bioengineering)
Material Jetting (MJT) 3D printing (3DP) is a specific technology that deposits photocurable droplets of material and colored inks to fabricate objects layer-by-layer. The high resolution and full color capability render MJT 3DP an ideal technology for 3DP in medicine as evidenced by the 3DP literature. The technology has been adopted globally across the Americas, Europe, Asia, and Australia. While MJT 3D printers can be expensive, their ability to fabricate highly accurate and multi-color parts provides a lucrative opportunity in the creation of advanced prototypes and medical models. The literature on MJT 3DP has expanded greatly as of late, in part aided by the lowering costs of the technology, and this report is the first review to document the applications of MJT in medicine. Additionally, this report portrays the technological information behind MJT 3DP, cases involving fabricated MJT 3DP models from the University of Cincinnati 3DP lab, as well as the challenges of MJT in a clinical setting, including cost, expertise in managing the machines, and scalability issues. It is expected that MJT 3DP, as imaging and segmentation technologies undergo future improvement, will be best poised with representing the voxel-level-variations captured by radiologic-image-sets due to its capacity for voxel-level-control.